Impact of pursed lip breathing in improving exercisenduranceIn non-spontaneous pursed lip breathing chronic obstructive pulmonary disease patients. - M.MANIKUMAR; P.SANKARA KUMARAN; T.S.MUTHU KUMAR; A.N.SUNDARESAN; G.DEEPTHI (International Journal of Pharma and Bio Sciences, 2017)
COPD is a progressive disease associated with cough, mucus, wheezing, shortness of breath. This study was done to find out the effects of pursed lip breathing in terms of improvement in the endurance and reduction in exertional dyspnea among COPD patients. Thirty subjects were taken from Saveetha medical college and hospital and they were equally divided into two groups. The pre test evaluation was done using six minute walk test and Borgs scale. Group A was given six minute walk along with pursed lip breathing and Group B was given six minute walk alone for fifteen days. On fifteenth day post test values were taken. The comparison of pre test and post test values were done within and between the groups using t tests. The pre test and post test values of Group A and Group B for six minute walk test is 359.16 & 414.23, 360.66 & 383.06. The pre test and post test values of Group A and Group B for Bores scale is 18.13 & 17.46, 17.53 & 18.06. This study concludes that there is a significant impact of pursed lip breathing on improving endurance and reducing exertional dyspnea in Group A treated with six minute walk along with pursed lip breathing.